SCALING RICEADVICE AND SUSTAINABLE RICE PLATFORM: INSIGHTS AND LESSONS LEARNED FROM 2022 TO 2025 - Suh, Neville Ndohnwi; Guindo, Samuel; Guindo, Jonathan; Dossou Yovo, Elliott Ronald (2025)
Food and nutritional insecurity remain major challenges in Mali, and projections indicate that the situation may worsen, particularly in conflict-affected areas where livelihoods depend on agriculture. Moreover, the country is located in the ecologically fragile Sahel and is highly vulnerable to climate risks, impacting agricultural production and farmers' livelihoods. Given that extreme climate events are projected to worsen, there is a need to promote climate-smart agriculture (CSA) practices that support increased rice productivity and climate resilience. Since 2022, the AICCRA Mali project has been promoting the adoption of various CSA practices in rice production, tailored to address key production constraints. Among the many innovations is also a digital advisory tool, RiceAdvice, that provides tailored recommendations of fertilizer type, quantity, and timing of application. Between 2022 and 2025, over 200,000 recommendations have been provided to rice farmers using RiceAdvice, with 38% beneficiaries being women. Moreover, between 2022 and 2025, 25500 recommendations have been provided to farmers (45% of whom were women) using RiceAdvice Lite. This training workshop aims to continue strengthening the knowledge and skills of extension agents, lead farmers, researchers, and other key stakeholders who are key to promoting the scaling of RiceAdvice Lite and the Sustainable Rice Platform innovations. The workshop also identifies key lessons and insights for the four-year implementation of CSA innovations in Mali, as well as key areas for improvement. The capacity-building workshop held on 20 November 2025 in Bamako brought together 26 researchers, extension agents, and project partners to strengthen stakeholder understanding of these tools, share field experiences, and reflect on scaling lessons from four years of implementation. 30% of the participants were female. Through hands-on installation sessions, guided demonstrations, interactive farmer simulations, and discussions on SRP standards and performance indicators, participants gained practical skills needed to deploy RiceAdvice Lite and SRP in rice-growing regions of Mali. The interactive sessions also allowed extension agents, researchers, and lead farmers to share their practical experiences. The workshop highlighted farmers’ enthusiasm for digital tools, their challenges related to seed access, fertilizer costs, and climate stress, and the need for stronger seed systems and agroecological integration. Key insights from the 2022–2025 scaling period point to the importance of capacity building, digital advisory tools, improved varietal dissemination, and integrated pest and disease management to strengthen climate resilience and advance Mali’s pathways toward rice self-sufficiency.